2023
DOI: 10.1021/acs.jpclett.3c02732
|View full text |Cite
|
Sign up to set email alerts
|

Case of the Bromine Vacancy in Cs4PbBr6

Byungkyun Kang,
Koushik Biswas

Abstract: Typically defect tolerance is equated with a lack of deleterious defects or with abundant defects creating only shallow levels. Here, we address the idea that deep defects, when unavoidable, do not guarantee harmful consequences. Using halogen vacancy as a common defect among halides, we explore its behavior in Cs 4 PbBr 6 . It is a large gap material (band gap of ∼4 eV) known for its green emission at ∼520 nm. We show that its Br-vacancy is indeed a deep defect as obtained from hybrid density functional calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…As we have reported for cesium lead iodide perovskites and Krishnakanth et al reported for cesium lead bromide perovskites, σ 2 for 0D-NCs is more than an order of magnitude higher than that of 3D-NCs. Observed higher TPA properties for 0D can be due to the involvement of defect states for 0D perovskites. , As it is now well reported that the strong fluorescence from Cs 4 PbBr 6 can be attributed to the lattice defects. ,, Since defect states for different nanocrystals are known to enhance multiphoton properties, ,, the higher TPA properties observed for 0D-NCs can probably be due to defect centers, which may be arising from halogen vacancies. ,, …”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…As we have reported for cesium lead iodide perovskites and Krishnakanth et al reported for cesium lead bromide perovskites, σ 2 for 0D-NCs is more than an order of magnitude higher than that of 3D-NCs. Observed higher TPA properties for 0D can be due to the involvement of defect states for 0D perovskites. , As it is now well reported that the strong fluorescence from Cs 4 PbBr 6 can be attributed to the lattice defects. ,, Since defect states for different nanocrystals are known to enhance multiphoton properties, ,, the higher TPA properties observed for 0D-NCs can probably be due to defect centers, which may be arising from halogen vacancies. ,, …”
Section: Resultsmentioning
confidence: 97%
“…[20][21][22][23][24][25][26][27][28]55,56 Since defect states for different nanocrystals are known to enhance multiphoton properties, [31][32][33][34][35]57,58 the higher TPA properties observed for 0D-NCs can probably be due to defect centers, which may be arising from halogen vacancies. [20][21][22][23][24][25][26][27][28]55,56 As reported in our reported σ 2 for 2D CsPbI 3 NPL is slightly higher than that reported for 2D CsPbBr 3 NPL by Alvarez et al 35 Interestingly, as reported in Table 3, our reported σ 2 for 1D CsPbI 3 NWs is much higher than that reported for 1D CsPbBr 3 NRs and 1D CsPb(I 0.15 Br 0.85 ) 3 NRs. 41 Due to very high two-photon absorption cross section (σ 2 ) values for 1D CsPbI 3 NWs, we have used two-photon fluorescence microscopic images to image those nanocrystals.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations